Schenkel [Georg Daniel] (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Schenkel." Produced by: Photographische Anstalt, Ed. Lange, Heidelberg, Westliche Hauptstrasse, No. 81. These dates are approximate.